Pulmonary Complications After Pediatric Stem Cell Transplant - Fitch, Taylor; Myers, Kasiani C.; Dewan, Maya; Towe, Christopher; Dandoy, Christopher (Frontiers in Oncology, 2021)
The number of disorders that benefit from hematopoietic stem cell transplants (HSCT) has increased causing the overall number of HSCT to increase accordingly. Disorders treated by HSCT include malignancy, benign hematologic disorders, bone marrow failure syndromes, and certain genetic diagnoses. Thus, understanding the complications, diagnostic work-up of complications and subsequent treatments has become increasingly important. One such category of complications includes the pulmonary system. While the overall incidence of pulmonary complications has decreased, the morbidity and mortality of these complications remain high. Therefore, having a clear differential diagnosis and diagnostic work-up is imperative. Pulmonary complications can be subdivided by time of onset and whether the complication is infectious or non-infectious. While most infectious complications have clear diagnostic criteria and treatment courses, the non-infectious complications are more varied and not always well understood. This review article discusses pulmonary complications of HSCT recipients and outlines current knowledge, gaps in knowledge, and current treatment of each complication. This article includes some adult studies as there is a significant paucity of pediatric data.